1983
DOI: 10.4992/psycholres1954.25.140
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blink rate during signal discrimination tasks

Abstract: Effects of stimulus modality, information processing activity and motor response on the blink rate were examined. In Experiment 1, visual and auditory stimuli were employed. The blink rate peaked just after a stimulus and then progressively decreased until thenext stimulus. The changes in the blink rate were similar for both the visual and the auditory stimulus conditions. In Experiment 2, only auditory stimuli were given to examine the effects of discriminative responses and motor responses on the blink rate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The results of numerical simulations in this study suggest that the variable threshold plays a critical role in producing a variety of IBI distributions, especially for the bimodal distribution. Numerous experimental studies have revealed that the blink rates are regulated by internal states of the participants during performing cognitive tasks (e.g., [ 6 , 11 ]). While we assumed that the variable threshold represented particular physiological fluctuations, a few plausible candidates of human internal states exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of numerical simulations in this study suggest that the variable threshold plays a critical role in producing a variety of IBI distributions, especially for the bimodal distribution. Numerous experimental studies have revealed that the blink rates are regulated by internal states of the participants during performing cognitive tasks (e.g., [ 6 , 11 ]). While we assumed that the variable threshold represented particular physiological fluctuations, a few plausible candidates of human internal states exist.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been hypothesized that such frequent blinking could play an important role in adaptive human behaviours [ 4 ], [ 5 ]. Participants in a laboratory experiment tended to blink immediately after the emergence of intermittently presented visual stimuli [ 6 ] indicating that people reliably receive visual information avoiding oversight errors. Similarly, researchers have reported that viewers were likely to blink at implicit breaks in expert storytelling performances [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pupil dilation and blinks rate have reflected variations in the subjects' cognitive demands or processing load on varied tasks such as translation language processing, reasoning, perception, sustained attention, and selective attention [8,40,36].…”
Section: Individual Differencesmentioning
confidence: 99%
“…In experiments, blink rates immediately increase after finishing cognitive tasks while blinks are suppressed during cognitive events. In the experiments, the number of sequential blinks, referred as “bursts” or “flurries”, correlates with the degree of cognitive load [10]. Most recently, a study revealed that human can learn to use strategic blinking to maximize obtained visual information under the constraint to keep humidity of eye surfaces [11].…”
Section: Introductionmentioning
confidence: 99%